2008
DOI: 10.1016/j.jasms.2008.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen atom scrambling in selectively labeled anionic peptides upon collisional activation by MALDI tandem time-of-flight mass spectrometry

Abstract: We have previously shown that peptide amide hydrogens undergo extensive intramolecular migration (i.e., complete hydrogen scrambling) upon collisional activation of protonated peptides (Jørgensen et al. J. Am. Chem. Soc. 2005, 127, 2785-2793. The occurrence of hydrogen scrambling enforces severe limitations on the application of gas-phase fragmentation as a convenient method to obtain information about the site-specific deuterium uptake for proteins and peptides in solution. To investigate whether deprotonated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…The consideration of such differences between positively-charged and negatively-charged ions served as a motivation for the study presented here. Finally, it is noted that some have argued that collision-induced dissociation (CID) should not be used in HDX structural studies because of the potential for HD scrambling [10, 27] while others have suggested some utility for HDX-MS/MS studies [1, 28]. Here we extend the latter consideration by presenting an initial approach that determines the accessibility of hydrogens on model structures obtained from molecular dynamics simulations (MDS).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The consideration of such differences between positively-charged and negatively-charged ions served as a motivation for the study presented here. Finally, it is noted that some have argued that collision-induced dissociation (CID) should not be used in HDX structural studies because of the potential for HD scrambling [10, 27] while others have suggested some utility for HDX-MS/MS studies [1, 28]. Here we extend the latter consideration by presenting an initial approach that determines the accessibility of hydrogens on model structures obtained from molecular dynamics simulations (MDS).…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, effectively testing such assumptions requires access to accurate structures obtained from MDS. Finally, at the time, site-specific deuterium uptake information to aid model development could not be obtained due to problems associated with hydrogen-deuterium (HD) scrambling during the ion fragmentation process[9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12]20 Interestingly, we have found that H/D scrambling is also prevalent in negative ion mode for CID of deprotonated peptides. 33 In this case, a "mobile deprotonation site" causes extensive internal rearrangement of deuterons initially located on the backbone amides. With the present knowledge of the prevalence of scrambling in protonated peptides and proteins, there is now a consensus that CID should not be used as an experimental tool to obtain information on the local deuterium uptake in solution.…”
Section: Collision-induced Dissociationmentioning
confidence: 99%
“…Also, the selective labeling with an N-terminal half devoid of deuterium ensures a maximal sensitivity for detecting and measuring the level of gas-phase hydrogen scrambling. Using such peptides, we have demonstrated that CID [9,[18][19][20] cause extensive hydrogen scrambling, while electron capture dissociation (ECD) [11], electron transfer dissociation (ETD) [10] and MALDI in-sourcedecay [21] proceed with a negligible level of hydrogen scrambling. These fragmentation techniques are thus available as experimental tools in either a "bottom-up" [22] or a "top-down" [23][24][25] approach to determine site-specific deuterium levels of proteins from solution H/D exchange experiments provided that any excessive vibrational excitation is avoided prior to the fragmentation event.…”
Section: Electron Transfer Dissociation Of K 2 D 6 Iikiikmentioning
confidence: 99%